S6Ks isoforms contribute to viability, migration, docetaxel resistance and tumor formation of prostate cancer cells. Issue 1 (December 2016) - Amaral, Camila; Freitas, Lidia; Tamura, Rodrigo; Tavares, Mariana; Pavan, Isadora; Bajgelman, Marcio; Simabuco, Fernando
Abstract Background The S6 Kinase (S6K) proteins are some of the main downstream effectors of the mammalian Target Of Rapamycin (mTOR) and act as key regulators of protein synthesis and cell growth. S6K is overexpressed in a variety of human tumors and is correlated to poor prognosis in prostate cancer. Due to the current urgency to identify factors involved in prostate cancer progression, we aimed to reveal the cellular functions of three S6K isoforms–p70-S6K1, p85-S6K1 and p54-S6K2–in prostate cancer, as well as their potential as therapeutic targets. Methods In this study we performed S6K knockdown and overexpression and investigated its role in prostate cancer cell proliferation, colony formation, viability, migration and resistance to docetaxel treatment. In addition, we measured tumor growth in Nude mice injected with PC3 cells overexpressing S6K isoforms and tested the efficacy of a new available S6K1 inhibitor in vitro. Results S6Ks overexpression enhanced PC3-luc cell line viability, migration, resistance to docetaxel and tumor formation in Nude mice. Only S6K2 knockdown rendered prostate cancer cells more sensitive to docetaxel. S6K1 inhibitor PF-4708671 was particularly effective for reducing migration and proliferation of PC3 cell line. Conclusions These findings demonstrate that S6Ks play an important role in prostate cancer progression, enhancing cell viability, migration and chemotherapy resistance, and place both S6K1 and S6K2 as a potential targets in advanced prostate cancer. We also provide evidence that S6K1 inhibitor PF-4708671 may be considered as a potential drug for prostate cancer treatment.